Stimuli-responsive delivery strategies for controllable gene editing in tumor therapeutics. Issue 38 (7th September 2022) - Ji, Yu; Fan, Liansheng; Qu, Suchen; Han, Xin
Abstract : The CRISPR system has attracted significant attention due to its great potential in tumor therapy. Abstract : The CRISPR system has attracted significant attention due to its great potential in tumor therapy. Developing effective, precise and safe delivery vectors is a prerequisite for CRISPR applications. Some disease-related biological signals provide a rationale for the development of precise delivery vehicles for stimuli-response delivery. Therefore, combining the linker of endogenous signal and exogenous signal stimulus responses with the nanocarrier is the key to designing and synthesizing the controllable release vector in stimuli-response delivery. This review summarizes the synthesis of stimuli-responsive nanocarriers by designing key chemical structures to achieve controllable release. Nanocarriers controlled by biochemical or physical signals are then discussed. Finally, potential challenges and prospects for existing nanocarriers are discussed.